Analisis Penerapan Akuntansi Pemerintahan Good Governance di Provinsi Jawa Barat - Natalia Br. Sitorus, Mawar; Nabila Khalid, Anggi Aulia; Nikmas Hutapea, Katarina; Rizki, Sri; Erica, Deliana (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2023)
This research was conducted against the backdrop of a phenomenon in which an Indonesian Supreme Audit Agency (BPK-RI) audit also explained particularly the poor quality of financial reporting by the Regional, Provincial and City District Governments. This research was investigated through a survey and supported by the existence of a theory to develop a research model designed to examine the quality of financial reporting from Local Governments that are relevant to the competence of Internal Accountants, the principle of good governance is the application of accrual-based government accounting standards. The previous survey was carried out for two years targeting the provincial/regency/city/district governments of West Java and Banten which reached 37 local governments. Data were analyzed using a structural equation model, processed using Smart PLS. The advantage of this research is that it can contribute scientifically to the science of public sector accounting and solve problems for local governments in implementing related tasks to improve the quality of local government financial reporting. The results of the study show that the competence of internal accountants has a significant effect on the quality of financial reporting, especially in local government. The principles of good governance and the application of accrual-based government accounting standards have a positive effect on regional government financial reports